The link between gas diffusion and carbonation in hardened cement pastes. (September 2019) - Dutzer, Vincent; Dridi, Wissem; Poyet, Stéphane; Le Bescop, Patrick; Bourbon, Xavier
Abstract: The influence of atmospheric carbonation on gas diffusion was investigated using four hardened cement pastes (CEM I, CEM III/A, CEM V/A, and a low-alkalinity binder) with common water-to-binder ratio (0.4). The diffusivity of the non‑carbonated and carbonated pastes with respect to helium and nitrogen was measured at different relative humidities. Carbonation decreased the diffusivity of the CEM I paste, whereas that of the other binders significantly increased after carbonation. These results show the competition between porosity clogging and cracking induced by carbonation. The consequences of carbonation are therefore believed to depend on the considered binder. Clogging dominates in ordinary Portland cement (OPC), leading to a decrease in its transport properties after carbonation; cracking dominates in blended cements, leading to a significant increase in its transport properties after carbonation.